2021
DOI: 10.1007/s00062-021-01079-1
|View full text |Cite
|
Sign up to set email alerts
|

Stent-Based Retrieval Techniques in Acute Ischemic Stroke Patients with and Without Susceptibility Vessel Sign

Abstract: Background and Purpose Randomized controlled trials have challenged the assumption that reperfusion success after mechanical thrombectomy varies depending on the retrieval techniques applied; however, recent analyses have suggested that acute ischemic stroke (AIS) patients showing susceptibility vessel sign (SVS) may respond differently. We aimed to compare different stent retriever (SR)-based thrombectomy techniques with respect to interventional outcome parameters depending on SVS status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…13 Multiple studies have also attempted to individually demonstrate the role of SVS in MCA territory or posterior circulation infarcts. 9, 14, 15 Our study showed that SVS was observed in 73 (68.9%) patients with LVO, in line with the study by Bourcier et al, which showed 76% of patients were SVS positive with anterior circulation ischemic stroke, and indeed higher than the observed value of 47.4% SVS positivity in the 2004 study by Cho et al 11…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…13 Multiple studies have also attempted to individually demonstrate the role of SVS in MCA territory or posterior circulation infarcts. 9, 14, 15 Our study showed that SVS was observed in 73 (68.9%) patients with LVO, in line with the study by Bourcier et al, which showed 76% of patients were SVS positive with anterior circulation ischemic stroke, and indeed higher than the observed value of 47.4% SVS positivity in the 2004 study by Cho et al 11…”
Section: Discussionsupporting
confidence: 89%
“…13 Multiple studies have also attempted to individually demonstrate the role of SVS in MCA territory or posterior circulation infarcts. 9,14,15 Our study showed that SVS was observed in 73 (68.9%) patients with LVO, in line with the study by Bourcier et al, which showed 76% of patients were SVS positive with anterior circulation ischemic stroke, and indeed higher than the observed value of 47.4% SVS positivity in the 2004 study by Cho et al 11 In examining studies that evaluated the sensitivity and specificity of SVS for detecting major intracranial occlusions across various vascular territories, it is noteworthy to mention the study conducted by Lingegowda et al 4 In their study involving 48 patients, they reported that the sensitivity and specificity of the "susceptibility sign" for detecting MCA occlusion were 77% and 100%, respectively (10 out of 13 cases). This suggests that SVS demonstrated high specificity in identifying MCA occlusion, accurately differentiating it from non-occluded cases.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates and screening for the titles and abstracts, 63 papers remained for full text review from which we excluded 58 papers (overlapping population, n=2; wrong outcome or no outcome reported, n=41; review, n=4; combined technique only used as salvage, n=2; unable to extract data, n=2; other endpoints, n=4; other, n=1). Finally, we included five studies in our meta-analysis,17 18 26–28 which included four cohort studies and one randomized trial. The quality of all of the included articles was high.…”
Section: Resultsmentioning
confidence: 99%
“…Prediction of and clinical outcome for EVT is an active field of research showing promising results [ 4 10 ]. Specifically, multiple studies have investigated the influence of the vascular access to the occlusion site.…”
Section: Introductionmentioning
confidence: 99%